Exploring reuse criteria for emergency temporary wooden housing- emphasis on local reuse and relocation - Ziyu Jiao; Aya Ishigaki; Hideaki Sumikura (Journal of Asian Architecture and Building Engineering)
During natural disasters, numerous temporary wooden houses are typically constructed, but regrettably, they are seldom repurposed and are instead disassembled once their two-year supply period expires. This study, therefore, delves into the criteria governing the construction and subsequent reuse of temporary wooden houses through discriminant analysis. The primary hindrance to their reutilization lies in the perception of local governments, which often regard these structures as strictly temporary dwellings, thus showing no intention of reusing them. However, the factors contributing to the reusability of temporary wooden houses extend beyond this singular perspective. A predictive equation is employed to determine a wooden temporary house’s potential for reuse by assessing the discriminant result derived from the discriminant equation. The pivotal factors found to influence reuse are the site area per unit and the construction method, which play a crucial role in both local and relocation reuse scenarios.